Analisis Penanganan Konflik Pembangunan Gereja Baptis Indonesia di Tlogosari Semarang - Wijayanto, Wahyudi Sri (Hanifiya: Jurnal Studi Agama-Agama, 2021)
The construction of the Tlogosari Church in Semarang, which had issued its 1998 building permit, became a polemic. The residents of Malangsari RT 06 / RW 07 disagreed with constructing a church in the area. On the other hand, the church establishment permit was issued in 1998. The construction of the Indonesian Baptist Church caused the Malangsari community as cheated by the signature of the Tlogosari Indonesian Baptist Church. So, viewed with an analysis of stages of conflict and a timeline that describes the chronology of time before the conflict occurred until, after the conflict ended, the resolution of the conflict could occur through mediation, which was carried out several times. The end of the mediation led by the head of the Semarang National Human Rights Commission was that the City Government gave a building permit (IMB) to the Tlogosari Indonesian Baptist Church to rebuild.